2010
DOI: 10.3390/toxins2030326
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Nuclear Instability in Archived Renal and Upper Urinary Tract Tumours with Putative Ochratoxin Aetiology

Abstract: DNA ploidy measurement has been applied uniquely to wax-embedded tissue of primary renal cell and metastatic tumours of a key experimental researcher on porcine ochratoxicosis, a control, and four transitional cell carcinomas from cases of Balkan endemic nephropathy. Primary renal tumour was diploid, and hyperdiploid metastasis was within the lower ploidy range for typical renal cell carcinoma. Three Balkan primary tumours showed extensive aneuploidy indicating marked nuclear instability, similar to model rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Further, a predictive animal-model role for the rat in human RCC aetiology seems at present insecure. Notably in the particular case of the late Palle Krogh, whose premature demise from a metastasising RCC might have come from professional experimental exposure to OTA for several years, the primary renal tumour was diploid [21] in marked histopathological contrast with the aneuploidy of OTA/rat carcinomas [22]. This makes an aetiological connection between experimental rat and natural human difficult for OTA, particularly since experiment needs a vastly greater dosage of the mycotoxin than is naturally available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, a predictive animal-model role for the rat in human RCC aetiology seems at present insecure. Notably in the particular case of the late Palle Krogh, whose premature demise from a metastasising RCC might have come from professional experimental exposure to OTA for several years, the primary renal tumour was diploid [21] in marked histopathological contrast with the aneuploidy of OTA/rat carcinomas [22]. This makes an aetiological connection between experimental rat and natural human difficult for OTA, particularly since experiment needs a vastly greater dosage of the mycotoxin than is naturally available.…”
Section: Discussionmentioning
confidence: 99%
“…; similar to that for case 5 above), and is considered together with metastases that are also from archived paraffin-embedded tissues. Renal tumours in cases 2, 3 and 6 had already been designated deoxyribonucleic acid (DNA) aneuploid [21] (in which, specifically for case 6 here, see Table 1, rat 5, Figure 1L and Figure 2E). The extensive renal distortion/destruction by most of these tumours has precluded exclusion of their origin from transitional cell epithelia of the renal pelvis until the present study.…”
Section: Methodsmentioning
confidence: 99%
“…A section of a Danish renal cell carcinoma (diploid) [9] also gave a negative response, as did a Romanian human angiosarcoma. Reciprocal analysis of the angiosarcoma of rat case 4 in Romania showed that the tissue did not express the human proteins CD31, CD34 or D2-40.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly archived human tumour tissues were from Denmark (a metastasising renal cell carcinoma [9]) and Romania (County Hospital, Timisoara; four transitional cell carcinomas from cases of Balkan endemic nephropathy [9]); details of their histopathology and DNA ploidy distribution have also been published [9]. A Romanian human angiosarcoma was also used.…”
Section: Methodsmentioning
confidence: 99%
“…A very recent publication (45) reports enhanced AA-DNA adduct formation by OTA in rats, with indirect implication for ideas about OTA in BEN tumourigenesis. This had already been recognised generically (46) for OTA on account of common complex aneuploidy in rat renal/OTA tumours and Romanian BEN urothelial tumours. However, it is important to remember that, although mis-repair of adducts can be a route to cancer, occurrence only indicates exposure, and exposure is an important dimension of satisfying Koch's postulates in epidemiology.…”
Section: Aa/dna Adductsmentioning
confidence: 87%